NiO-based memristor with three resistive switching modes - Li, Ya; Fang, Paiwen; Fan, Xihua; Pei, Yanli (Semiconductor science and technology, 2020)
In this research, solution-processed NiO-based memristors have been demonstrated with three resistive switching modes, including analog resistive switching, volatile threshold resistive switching and nonvolatile digital resistive switching, where the specific behavior is determined by the applied bias voltage and compliance current. The analog resistive switching is achieved via local oxygen ion migration at the NiO/Ag interface under low voltage stress. Based on this resistive switching mode, several synaptic functions are mimicked. When the device is stressed using a high voltage and a low compliance current, the device behavior changes to volatile threshold resistive switching. This behavior allows spiking neuron functions to be simulated. Furthermore, under application of a high compliance current, the device behavior converts to nonvolatile digital resistive switching. Ag filament formation and rupture processes are considered to be the mechanism behind the volatile threshold and nonvolatile resistive switching behavior. This multifunctional NiO-based memristor will provide a basis for fabrication of memory devices, analog circuits and artificial neural networks.